Evaluation of the Effect of Palashadi Varti in the management of Shweta Pradara (Abnormal Vaginal Discharge) on Clinical Parameters - Akshita; Soni Kapil (AYUSHDHARA, 2025)
Abnormal Vaginal Discharge can be correlated to Shweta Pradara is detailed in texts like Sharagdhar Samhita, Bhavprakash, and Yogratnakar. Commentator Chakrapani has explained the word Pandura-Asrigdara as Shwetapradar in his commentary on Charak Samhita. This condition often signals underlying genital tract pathologies and may present as thick, viscid, and foul-smelling discharge, particularly when caused by infections. Common pathogens include Gardnerella, Chlamydia, Trichomonas, and Candida albicans. AIM & OBJECTIVES: To assess the effect of the trial drug Palashadi Varti in the Management of Shwetapradar and to evaluate the comparative efficacy of the trial drug with modern drug. MATERIAL & METHODS: With Ethical Committee approval and informed consent, 210 patients were randomly assigned to two groups. In one group, Palashadi Varti at night was given for 7 days. From baseline to 7th day based on assessment criteria per-speculum examination was done. A comparison of categorical variables was done using an appropriate statistical test. RESULTS: Palashadi Varti potentially had comparable effects to the conventional treatment but the recurrence rate was found more in conventional treatment. CONCLUSION: Palashadi Varti is an effective, side effects-free, patient-complaint herbal alternative for the management of abnormal vaginal discharge.